A high-resolution, 60 kyr record of the relative geomagnetic field intensity from Lake Towuti, Indonesia - Kirana, Kartika Hajar; Bijaksana, Satria; King, John; Tamuntuan, Gerald Hendrik; Russell, James; Ngkoimani, La Ode; Dahrin, Darharta; Fajar, Silvia Jannatul (Physics of the earth and planetary interiors, 2018)
•For magnetically strong Lake Towuti sediments, the ARM is the best normalizer.•We provide the magnetic stratigraphy of the western tropical Pacific region during 60 kyr BP.•The paleointensity record from Lake Towuti is reliable and in good agreement with global records. Past changes in the Earth’s magnetic field can be highlighted through reconstructions of magnetic paleointensity. Many magnetic field variation features are global, and can be used for the detailed correlation and dating of sedimentary records. On the other hand, sedimentary magnetic records also exhibit features on a regional, rather than a global scale. Therefore, the development of regional scale magnetic field reconstructions is necessary to optimize magnetic paleointensity dating. In this paper, a 60 thousand year (kyr) paleointensity record is presented, using the core TOW10-9B of Lake Towuti, located in the island of Sulawesi, Indonesia, as a part of the ongoing research towards understanding the Indonesian environmental history, and reconstructing a high-resolution regional magnetic record from dating the sediments. Located in the East Sulawesi Ophiolite Belt, the bedrock surrounding Lake Towuti consists of ultramafic rocks that render the lake sediments magnetically strong, creating challenges in the reconstruction of the paleointensity record. These sediment samples were subject to a series of magnetic measurements, followed by testing the obtained paleointensity records resulting from normalizing natural remanent magnetization (NRM) against different normalizing parameters. These paleointensity records were then compared to other regional, as well as global, records of magnetic paleointensity. The results show that for the magnetically strong Lake Towuti sediments, an anhysteretic remanent magnetization (ARM) is the best normalizer. A series of magnetic paleointensity excursions are observed during the last 60 kyr, including the Laschamp excursion at 40 kyr BP, that provide new information about the magnetic history and stratigraphy of the western tropical Pacific region. We conclude that the paleointensity record of Lake Towuti is reliable and in accordance with the high-quality regional and global trends.